You are on page 1of 46

METHODS

OF
PROOF
JOEROM D. ONOFRE
METHODS OF PROOF
v Trivial Proofs
v Vacuous Proofs
v Direct Proofs
v Indirect Proofs
v Proof by Cases
v Principles of Mathematical Induction
v Proofs Involving Quantifiers
v Disapproving Statement and
Counterexample
PROOF
It is a logical argument in which each
statement that you make is backed up
by a statement that is accepted as true.
TRIVIAL
PROOFS
Trivial Proofs : Conclusion holds without using the
hypothesis. A trivial proof can be given when the
conclusion is shown to be (always) true. That is, if q is
true then p → q is true.
Example 1:
��� � ∈ �, �� � �� �� ��� ������, �ℎ�� 2 �� � ����� ������.
Proof:
��� � ∈ �, ����� 2 �� � ����� ������, �ℎ� ���������� ��
������ ����, �� �ℎ�� ����������� ��������� �� ��������� ����. ∎
Not���:
We didn’t make any mention of hypothesis.
Example 2: ��� � ∈ �, �� � > 0, �ℎ�� �2 + 5 ≥ 0
Q - is always true
�2 ≥ 0 ��� ��� � ∈ ℝ and Z , 5 > 0
so �2 + 5 ≥ 0
Proof: Let x ∈ Z, Notice the conclusion is always true, this
is beacuse for any real number and hence, for any integer, we
have shown that the 2 scenario is always greater than or equal to 0.
Therefore,
�2 + 5 ≥ 0, this statement is trivially true. ∎
Example 3: ��� � ∈ ℝ, �� �2 − 4 ≥ 0, �ℎ�� �2 + 4 ≥ 0
Q - is always true
�2 ≥ 0 , 4 > 0
so �2 + 4 ≥ 0
Proof: Let x ∈ ℝ, Observe that the conclusion is always true,
beacuse we have seen for all � ∈ ℝ, where the
2 scenario is always greater than or equal to 0 and thus �2 + 4 ≥ 0,
we can conclude that this statement is trivially true. ∎
VACUOUS
PROOFS
Vacuous Proof: If p is a conjunction of other
hypotheses and we know one or more of these
hypotheses is false, then p is false and so p → q is
vacuously true regardless of the truth value of q.
Example 1: ��� � ∈ �, �� �2 < 0, �ℎ�� � �� �� ��� ������.
P - is always false
Proof:
Let x ∈ N, Notice that the hypothesis �2 < 0 is always false,
beacuse any square of natural number is always positive. Thus
the entire statement is vacuously true. ∎
Example 2:
��� � ∈ ℝ, �� � + 1 < 0, �ℎ�� �5 < 4.
P - is always false
� ≥ 0,
� +1≥0
Proof: Let x ∈ ℝ, By definition of absolute value, � ≥ 0,
and so � + 1 ≥ 0. This means that the hypothesis is always
false, Thus the entire statement is vacuously true. ∎
Example 3:
1 1
��� � ∈ �, �� � + < 2, �ℎ�� �2 + < 4.
� �2
P - is always false
1
n=1:1+ < 2 - false
1
1
n=2:2+ < 2 - false
2
1
n=3:3+ < 2 - false
3
Example 3:
1 1
��� � ∈ �, �� � + < 2, �ℎ�� �2 + < 4.
� �2
P - is always false
1
n �+ <2

�2 + 1 < 2�
�2 + 1 − 2� < 2� − 2�
�2 − 2� + 1 < 0
(� − 1) (� − 1) < 0
(� − 1)2 < 0 This must be false because for any square of natural number is ≥ 0. ∎
DIRECT
PROOFS
Direct Proof: We assume P is true, and together with
other establish properties, one should show that Q is
also true.
DEFINITIONS
Even Intergers: An even integer takes the form 2k for some
integer k.

Odd Integers: An odd integer takes the form 2k + 1 for some


integer k.

Perfect Square Integer: An integer is a perfect square when it


takes the form k2 for some integer k.

Divisivility of an Integer: An integer m is divisible by n when m


can be expressed as kn for some integer k. If m is divisible by n
we say that n divides m and we symbolize it as n �. So n � if
m = kn for some integer k.
Example 1:
Prove that the sum of two even numbers is even.
Suppose m and n are even numbers.
� + � = 2� + 2� = 2 (� + �)
� + � = 2� + 2� = 2�
� + � = 2�
Again by definition, this implies that � + � is also an even
number. ∎
Example 2:
Prove that the product of any two odd integer is odd.
Suppose m and n are odd numbers.
�� = (2� + 1)(2� + 1 ) = 4�� + 2� + 2� + 1
�� = (2� + 1)(2� + 1 ) = 2(2�� + � + � ) + 1
�� = 2 � + 1 Again by definition, this implies that �� is
also an odd number. ∎
Example 3:
Prove that for any integer n the number 2(�2 + � + 1) − (�2 + 1) is a perfect
square.
Let n be an� �������. We need to show that 2(�2 + � + 1) − (�2 + 1) is a perfect
square.
2(�2 + � + 1) − (�2 + 1) = 2�2 + 2� + 2 − �2 − 1
2(�2 + � + 1) − (�2 + 1) = �2 + 2� + 1
2(�2 + � + 1) − (�2 + 1) = (� + 1)(� + 1)
2(�2 + � + 1) − (�2 + 1) = (� + 1)2
2(�2 + � + 1) − (�2 + 1) = �2
Therefore, for any integer n, 2(�2 + � + 1) − (�2 + 1) is a perfect square. ∎
Example 4:
Prove that for all integers a, b, c, if a � and b �, �ℎ�� � �
Suppose a, b, c are integers such that a � and b �.
Our next step is to show that � �.
a � �ℎ�� � = �� ��� ���� ������� �. ���� , �����
b � �ℎ�� � = �� ��� ���� ������� �. ����� � = �� ��� � = �� �� ℎ���,
� = �� = �(��) = (��)�
� = ��
Therefore, we can conclude that � � �� ������������ �� ������������ ∎
INDIRECT
PROOFS
In proving by contraposition, we assume the negation
of the conclusion. It should lead to the negation of the
hypothesis.

In proving by contradiction, we prove a claim p by


showing that its negation ~p leads to a contradiction.
Example 1:
Prove that �2 is even then n is even.
Assume that n is not even; that is an odd number. We need to show that �2 is
an odd number.
If n is an odd number then it takes the form 2� + 1 for some integer m.
�2 = (2� + 1)2
�2 = 4�2 + 4� + 1
�2 = 2(2�2 + 2�) + 1
�2 = 2� + 1
This implies that if n is an odd number, then �2 is also an odd number.
Since we have proven that the contrapositive is true, we can now conclude that its
conditional form is correct. Therefore, If �2 is even then n is even. ∎
Example 2:
Let x be an integer. Prove by contraposition that �2 − 4� + 3 is even, then x is odd.
Suppose x is even . Hence, we can write x as 2k for some integer k.
� = 2�
�2 − 4� + 3
(2�)2 − 4(2�) + 3
4�2 − 8� + 3
2(2�2 − 4� + 1) + 1
2� + 1
This means that �2 − 4� + 3 is an odd which is the negation of the assumption.
Therefore, if �2 − 4� + 3 is even, then x is odd. ∎
Example 3:
Prove that if a square of a number is odd, then the number must be odd.
First we let n be number. Assume the contrary, that is �2 is odd but n is even.
Since, n is even it can be written as n = 2k for some integer k.
� = 2�
�2 = (2�)2
�2 = 4�2
�2 = 2(2�2 )
�2 = 2�
This means that �2 is divisible by two, or equivalently �2 is even, which contradicts our
assumption. Therefore, the number must be odd. ∎
PROOF BY CASES
You can sometimes prove a statement by:

1. Dividing the situation into cases which exhaust all


the possibilities; and

2. Showing that the statement follows in all cases.

Note : It’s important to cover all the possibilities.


Example 1a:
If � ∈ �, then �2 + 3� + 5 is an odd integer.
Ca�� 1: � �� ����, then � = 2� where � ∈ �
� = 2�
�2 + 3� + 5 = (2�)2 + 3(2�) + 5
�2 + 3� + 5 = 4�2 + 6� + 5
�2 + 3� + 5 = 2(2�2 + 3� + 2) + 1
�2 + 3� + 5 = 2� + 1
Therefore, if �2 + 3� + 5 is an odd integer. ∎
Example 1b:
If � ∈ �, then �2 + 3� + 5 is an odd integer.
Ca�� 2: � �� ���, then � = 2� + 1 where � ∈ �
� = 2� + 1
�2 + 3� + 5 = (2� + 1)2 + 3(2� + 1) + 5
�2 + 3� + 5 = 4�2 + 4� + 1 + 6� + 3 + 5
�2 + 3� + 5 = 4�2 + 10� + 9
�2 + 3� + 5 = 2(2�2 + 5� + 4) + 1
�2 + 3� + 5 = 2� + 1
Therefore, if �2 + 3� + 5 is an odd integer. ∎
Example 2:
If � �� �� �������, then � ≤ �2 .
Ca�� 1: � ≤ − 1, � ≤ �2 = − 1 ≤ (1)2 = − 1 ≤ 1.
Ca�� 2: � = 0, � ≤ �2 = 0 ≤ (0)2 = 0 ≤ 0.
Ca�� 3: � ≥ 1, � ≤ �2 = 1 ≤ (1)2 = 1 ≤ 1.

Since our inequality � ≤ �2 is true for all possible cases, We can conclude
that � ≤ �2 for all integers. ∎
MATHEMATICAL
INDUCTION
a. P1 is true (that is, the statement is true for n = 1).

b. If P(n) is true for n = k, then P(n) is true for n = k+1.


Example 1:
Use induction to prove that the conjecture is true
2 + 4 + 6 + . . . + 2� = �(� + 1)
Condition 1: P(1) is true for n = 1
2 + 4 + 6 + . . . + 2� = �(� + 1)
2(1) = 1(1 + 1)
2 = 1(2)
2 = 2
Hence, the formula is true for n = 1.
Example 1:
Use induction to prove that the conjecture is true
2 + 4 + 6 + . . . + 2� = �(� + 1)
Condition 2: If P(n) is true for n = k, then P(n) is true for n = k+1.
2 + 4 + 6 + . . . + 2� = �(� + 1)
2 + 4 + 6 + . . . + 2� + �(� + 1) = �(� + 1)
�(� + 1) + 2(� + 1) = � + 1(� + 1 + 1)
�2 + � + 2� + 2 = � + 1(� + 2)
�2 + 3� + 2 = (� + 1)(� + 2)
(� + 1)(� + 2) = (� + 1)(� + 2)
Hence, by the principle of mathematical induction than P(n) is true for all natural number n. ∎
Example 2:
�(�+1)
Using mathematical induction prove that, 1 + 2 + 3 + . . . + � =
2

for all positive integer n.


�(�+1)
Condition 1: P(1) is true for n = 1 � =
2

1(1 + 1)
1 =
2
1(2)
1 =
2
2
1 =
2
1 =1
Hence, the formula is true for n = 1.
Example 2:
�(�+1)
Using mathematical induction prove that, 1 + 2 + 3 + . . . + � =
2

for all positive integer n.


Condition 2: If P(n) is true for n = k, then P(n) is true for n = k+1.
�(� + 1)
1 + 2 + 3 + ... + � = �(� + 1) + 2(� + 1) (� + 1)(� + 2)
2 =
2 2
� + 1(� + 1 + 1)
1 + 2 + 3 + ... + � + � + 1 = (� + 1) + (� + 2) (� + 1)(� + 2)
2 =
2 2
�(� + 1) (� + 1)(� + 2)
+ �+1 = Therefore, the formula is true for all positive
2 2
�(� + 1) �+1 (� + 1)(� + 2) integers n. ∎
+ =
2 1 2
Example 3:
�(�+1)(2�+1)
Using mathematical induction prove that, 12 + 22 + 32 + . . . + �2 =
6

for all positive integer n.


�(�+1)(2�+1)
Condition 1: P(1) is true for n = 1 �2 =
6
1(1+1)(2(1)+1)
(1)2 =
6
1(2)(3)
1 =
6

6
1 =
6
1 = 1
Hence, the formula is true for n = 1.
Example 3:
�(�+1)(2�+1)
Using mathematical induction prove that, 12 + 22 + 32 + . . . + �2 =
6

for all positive integer n.


Condition 2: If P(n) is true for n = k, then P(n) is true for n = k+1.
�(� + 1)(2� + 1)
12 + 22 + 32 + . . . + �2 =
6
�+1(�+1+1)(2(�+1)+1)
12 + 22 + 32 + . . . + �2 + (� + 1)2 =
6

� + 1(� + 1 + 1)(2(� + 1) + 1)
12 + 22 + 32 + ... + �2 + (� + 1)2 =
6
(� + 1)(� + 2)(2� + 3)
12 + 22 + 32 + . . . + �2 + (� + 1)2 =
6
Example 3:
�(�+1)(2�+1)
Using mathematical induction prove that, 12 + 22 + 32 + . . . + �2 =
6

for all positive integer n.


Condition 2: If P(n) is true for n = k, then P(n) is true for n = k+1.
(� + 1)(� + 2)(2� + 3)
12 + 22 + 32 + ... + �2 + (� + 1)2 =
6
�(� + 1)(2� + 1) (� + 1)(� + 2)(2� + 3)
12 + 22 + 32 + ... + + (� + 1) =
2
6 6
�(� + 1)(2� + 1) + 6(� + 1)2 (� + 1)(� + 2)(2� + 3)
12 + 22 + 32 + . . . + =
6 6
(�+1)[�(2�+1)+ 6(�+1)] (�+1)(�+2)(2�+3)
12 + 22 + 32 + . . . + =
6 6
Example 3:
�(�+1)(2�+1)
Using mathematical induction prove that, 12 + 22 + 32 + . . . + �2 =
6

for all positive integer n.


Condition 2: If P(n) is true for n = k, then P(n) is true for n = k+1.
(�+1)[�(2�+1)+ 6(�+1)] (�+1)(�+2)(2�+3)
12 + 22 + 32 + . . . + =
6 6

(� + 1)[(2�2 + �) + (6� + 6)] (� + 1)(� + 2)(2� + 3)


12 + 22 + 32 + ... + =
6 6
(� + 1)(2�2 + 7� + 6) (� + 1)(� + 2)(2� + 3)
12 + 22 + 32 + . . . + =
6 6
(� + 1)(� + 2)(2� + 3) (� + 1)(� + 2)(2� + 3)
12 + 22 + 32 + . . . + =
6 6
�(�+1)(2�+1)
Therefore, 12 + 22 + 32 + . . . + �2 = 6
for all positive integer n. ∎
PROOFS
INVOLVING
QUANTIFIERS
Quatifiers are words that refer to quantifies such as
“some” or “all”. It tells for hows many elements a given
predicate is true.
Universal Quantifier - The Universal Quatifification of P(x) is the
statement
“P(x) for all values of x in the domain”.
Notation:

∀� �(�)
For all x, P(x)
For every x, P(x)
where ∀ is called the universal quantifier
Universal Quantifier - The Universal Quatifification P(x) is the
statement
“P(x) for all values of x in the domain”.
Domain or Domain of Discourse
A domain specifies the possible values of a variable under consideration.
For example: Let P(x) is the statement � + 1 > � and let us assumme
that the domain is a set of all positive integers.
�(1) : 1 + 1 > 1 ����
�(2) : 2 + 1 > 2 ����
∀� �(�) �� ���� ����� �ℎ� ������ �� �������� ��������. ∎
Existential Quantifier - The Universal Quatifification of P(x) is the
proposition
“There exists an element x in the domain such that P(x).
Notation:
∃� �(�)
There is an x such that P(x)
There is at least one x such that P(x)
For some x P(x)
where ∃ is called the existential quantifier
Note: Specifying the domain is important. Without domain, the statement
∃� �(�) has no meaning.
Existential Quantifier - The Universal Quatifification of P(x) is the proposition
“There exists an element x in the domain such that P(x).
For Example: What is the thruth value of ∃� �(�), where P(x) is the statement �2 >
10 and the universe of discourse consists of positive integers not exceeding 4?
Solution: Domain 1, 2, 3, ��� 4
P(1) : 12 > 10 False
P(2) : 22 > 10 False
P(3) : 32 > 10 False
P(4) : 42 > 10 True

∃� �(�) is true : P(1) ˅P(2) ˅P(3) ˅P(4). ∎


DISAPPROVING
STATEMENT AND
COUNTEREXAMPLE
A counterexample is an example that disproves a universal (“for all”)
statement. Obtaining counterexamples is a very important part of
mathematics, because doing mathematics requires that you develop
a critical attitude toward claims. When you have an idea or when someone
tells you something, test the idea by trying examples. If you find a
counterexample which shows that the idea is false, that’s good: Progress
comes not only through doing the right thing, but also by correcting your
mistakes.
Example. Give a counterexample to the statement
“If n is an integer and n 2 is divisible by 4, then n is
divisible by 4.”
To give a counterexample, We have to find an integer n
such n2 is divisible by 4, but n is not divisible by 4 — the “if”
part must be true, but the “then” part must be false.
Consider n = 6. Then n2 = 36 is divisible by 4, but n = 6 is not
divisible by 4. Thus, n = 6 is a counterexample to the
statement. ∎
Example. Explain what you must do to disprove the statement:
(a) “All professors like pizza”.
(b) “For every real number x, (x + 1)2 = x2 + 1”.
Solution:
(a) To disprove “All professors like pizza”, you must find a professor who does not like
pizza. ∎
(b) To disprove the statement “For every real number x,
(x + 1)2 = x2 + 1”, you must find a real number x for which

(� + 1)2 ≠ �2 + 1.

(1 + 1)2 ≠ (1)2 + 1

(2)2 ≠ 1 + 1.
4 ≠ 2. ∎
THANK YOU
FOR
LISTENING!

You might also like